Angels in the outfield [videorecording (DVD)] - Kingsley, Dorothy; Wells, George, 1909-2000; Sloan, Holly Goldberg, 1958-; Glover, Danny; Danza, Tony; Fricker, Brenda; Gordon-Levitt, Joseph, 1981-; Lloyd, Christopher, 1938-; Edelman, Randy; Green, Bruce; Leonetti, Matthew F., 1941- (Disney DVD., 2002)
The California Angels are a struggling baseball team praying to win a pennant. Their luck changes as their biggest fan, 11-year-old Roger, begins giving the coach tips from a real live angel. The team not only climbs back into the pennant race, but learns to believe in themselves.